CUSTOMER ASSESSMENT OF QUALITY OF TRANSPORT (Perner's Contacts, 2011)
This article aims to understand the requirements imposed on the quality of passenger transport and public opinion evaluation of the quality of passenger service by the customer. It is intended for providers of public transport as a source of information in present time.